Atmospheric electric parameters and micrometeorological processes during the solar eclipse on 15 January 2010. Issue 11 (3rd June 2013) - Kumar, C. P. Anil; Gopalsingh, R.; Selvaraj, C.; Nair, K. U.; Jeyakumar, H. Johnson; Vishnu, R.; Muralidas, S.; Balan, N.
Abstract : [1] Indian scientists got the unique opportunity to study the near‐Earth environment during a long annular solar eclipse at the end of the last long deep solar minimum, on 15 January 2010. Continuous high time resolution records of the atmospheric electric parameters and meteorological parameters were made at Tirunelveli (8.07°N, 77.08°E, 35 m Above Mean Sea Level (AMSL) and Braemore Hill (8.41°N, 76.59°E, 460 m AMSL) stations where the eclipse was during 11:07:57–15:06:52 IST with maximum obscuration (~90%) at 13:17:09 Indian Standard Time (IST). The recorded values of the parameters show marked deviations from those normally observed on control fair‐weather days. The ambient electric field underwent a large drop by up to 65% during the eclipse, and potential gradient showed epochs of enhancements during and after the eclipse until postsunset. The data also seem to reveal the long lasting paradox of conductivity enhancement during eclipse, which may be due to the eclipse induced upsurge of low winds or waves that brings high density of free space charges embedded in air parcels. Key Points: The paradox of conductivity enhancement during eclipse. The reduction in GCR flux. The cooling enables scavenging free space charges.